On the Complementarity of Regional and Global Trade - Coulibaly, Souleymane (Washington, DC: World Bank, 2012)
Sourcing intermediate goods efficiently is essential for a country's production capacity. Countries located in a neighborhood providing a wide range of intermediate goods cheaply available can take advantage of scale economies to reduce their production costs and improve their global competitiveness. Many empirical works have documented the sharp increase in intra-industry trade and particularly trade in intermediate goods within developed neighborhoods such as the EU, North America and Northeast Asia. But what about developing neighborhoods? This paper uses COMTRADE aggregate exports of capital goods, intermediate goods, consumer goods and raw materials for 2002-06 to evaluate how a country's import of intermediate goods from its neighbors impacts its global export performance. For Sub-Saharan African countries particularly, there is a strong positive correlation between countries previous regional import of intermediate goods and their current exports, indicating that developing neighborhoods are also experiencing such complementarity between regional and global trade, the relation being stronger beyond a threshold of global competitiveness. These results call for a two-pronged policy action encompassing regional and global integration and putting a sub-set of Sub-Saharan countries close to that global competitiveness threshold at the heart of a neighborhood growth strategy.